Grief and Bereavement in Parents After the Death of a Child in Low- and Middle-Income Countries - Michael J. McNeil; Eve Namisango; Jennifer Hunt; Richard A. Powell; Justin N. Baker (Children, 2020)
While great strides have been made in improving childhood mortality, millions of children die each year with significant health-related suffering. More than 98% of these children live in low- and middle-income countries (LMICs). Efforts have been made to increase access to pediatric palliative care (PPC) services to address this suffering in LMICs through policy measures, educational initiatives, and access to essential medicines. However, a core component of high-quality PPC that has been relatively neglected in LMICs is grief and bereavement support for parents after the death of their child. This paper reviews the current literature on parental grief and bereavement in LMICs. This includes describing bereavement research in high-income countries (HICs), including its definition, adverse effect upon parents, and supportive interventions, followed by a review of the literature on health-related grief and bereavement in LMICs, specifically around: perinatal death, infant mortality, infectious disease, interventions used, and perceived need. More research is needed in grief and bereavement of parents in LMICs to provide them with the support they deserve within their specific cultural, social, and religious context. Additionally, these efforts in LMICs will help advance the field of parental grief and bereavement research as a whole.